Manipulating photodissociation dynamics via an embedding UV pulse - Liu, Yan Rong; Bai, Xin; Nan, Quan Wei; Kimberg, Victor; Gong, Maomao; Yang, Yu Kun; Cheng, Yongjun; Chen, Jing; Vendrell, Oriol; Ueda, Kiyoshi; Rost, Jan-Michael; Zhang, Song Bin (Communications Physics, 2025)
Ultraviolet (UV) photodissociation provides valuable insights into fragmentation patterns and photochemical reactions. However, the limited overlap between vibrational bound states and continuum states hinders efficient quantum excitation. We address this challenge by embedding the ground bound potential into the dissociative continuum using a frequency-selected UV pulse. This pulse creates vibrational resonances by coupling the dissociative continuum with unpopulated vibrationally excited levels of the ground state, without initiating photoexcitation itself. Our findings demonstrate that the photodissociation spectra can be significantly manipulated by tuning the embedding pulse frequency to tailor the asymmetric profiles of the vibrational resonances. This is illustrated in our simulations of kinetic energy release spectra for both diatomic and polyatomic molecules. These proof-of-principle examples offer opportunities for manipulating the yield of photofragmentation and the pathways of photochemical reactions in various molecular systems.
Veröffentlicht: 14. August 2025
Gesehen am 21.01.2026